Utilization of Indigofera zollingeriana leaves meal in feed formulation to color brightness and growth in koi fish (Cyprinus carpio) - Mukti, Retno Cahya; Yulisman, Yulisman; Irmawati, Irmawati; Putra, Muhamad Sadina (Universitas Malikussaleh, 2024)
This study aims to determine the effect of the addition of Indigofera zollingeriana in feed formulations with different doses on the color brightness of koi fish. The research design was Completely Randomized Design (CRD) with five treatments and three replications. Treatment P0 was control (without the use of Indigofera leaf meal), P1 was the addition of 5% indigofera meal, P2 was the addition of 10% indigofera meal, P3 was the addition of 15% indigofera meal, and P4 was the addition of 20% indigofera meal. Fingerlings measuring 6 ± 1 cm with a stocking density of 1 fish for 2 L were reared for 30 days in this study. The results showed that P2 with a percentage of 10% Indigofera zollingeriana meal was the best treatment for the brightness of koi fish color (27.23). Still, they had no significant effect on the growth of absolute length (1.04 cm) and absolute weight (1.05 g), feed efficiency (23.08%), and survival rate (100%). The water quality obtained during maintenance was temperature 26-27oC, pH 6.1-7.2, dissolved oxygen 5.2-6.3 mg/L, and ammonia 0.02-0.036 mg/L.Keywords: Fish Color Brightness; Indigofera zollingeriana; Koi Fish